The Immune Modulating Properties of Mucosal-Associated Invariant T Cells - Ioannidis, Melina; Cerundolo, Vincenzo; Salio, Mariolina (Frontiers in Immunology, 2020)
Mucosal-associated invariant T (MAIT) cells are unconventional T lymphocytes that express a semi-invariant T cell receptor (TCR) α-chain (in humans mostly Vα7.2-Jα33/Jα20, in mice Vα19-Jα33) paired with a restricted number of TCR β-chains contributing to a limited TCR repertoire. The MAIT cell semi-invariant TCR recognizes vitamin B metabolites presented by a highly conserved major histocompatibility complex (MHC) class I like molecule, MR1. The vitamin B metabolites are produced by several bacteria and yeast, but not viruses. Nevertheless, viral infections can trigger MAIT cell activation in a TCR-independent manner, through the release of pro-inflammatory cytokines by antigen-presenting cells (APCs). Because of a memory phenotype, in response to local antigens MAIT cells rapidly release Interferon (IFN)-γ, tumour necrosis factor (TNF)-α and in some circumstances Interleukin (IL)-17 and IL-10, exerting an immunomodulatory role on the ensuing immune response. In addition to their anti-microbial role, recent research has shown that MAIT cells play a role in inflammatory diseases, cancer, tissue repair and immune homeostasis, showing diversity in their transcriptome dependent on their stimulation mode. These multifunctional innate-like T lymphocytes that are not donor restricted are therefore an interesting target for novel immunotherapeutic strategies. Further understanding of the molecular mechanisms underpinning MAIT cell activation and effector function will aid in clinically harnessing this unique cell subtype.